Sarcopenia: Prevalence and Prognostic Implications in Elderly Patients with Cardiovascular Disease. Issue 2 (1st July 2017) - Kamiya, Kentaro; Hamazaki, Nobuaki; Matsuzawa, Ryota; Nozaki, Kohei; Tanaka, Shinya; Ichinosawa, Yuta; Maekawa, Emi; Noda, Chiharu; Yamaoka‐Tojo, Minako; Matsunaga, Atsuhiko; Masuda, Takashi; Ako, Junya
Abstract: Aims: Sarcopenia has recently been given an ICD‐10 code. However, there have been no systematic investigations regarding the prevalence or prognostic value of sarcopenia in cardiovascular disease (CVD) according to the international consensus definition. The present study was performed to investigate the prevalence and prognostic value of sarcopenia in elderly patients with CVD. Methods and results: The study population consisted of 1603 admitted patients aged ≥ 65 years (74.4 ± 6.2 years, 1049 men) with CVD. Sarcopenia was defined according to the recommended diagnostic algorithm of the Asia Working Group for Sarcopenia. The endpoint for the study was all‐cause mortality. The overall sarcopenia prevalence rate was 29.7% (19.6% in men and 48.7% in women). The prevalence rates of sarcopenia across major diagnostic categories were as follows: acute coronary syndrome, 17.8%; post‐cardiac surgery, 31.8%; and heart failure, 35.2%. During the 2.3 ± 2.1‐year follow‐up period, 175 deaths occurred. Patients with sarcopenia showed higher risk of all‐cause mortality compared with non‐sarcopenic patients (adjusted hazard ratio: 1.44; 95% confidence interval: 1.01 – 2.05; P = 0.044). Conclusions: Sarcopenia is highly prevalent among elderly patients with CVD and is associated with increased mortality risk.